(untitled) (Revista Brasileira de Contabilidade e Gestão, 2014)
The agricultural sector is one of the largest consumers of water, with irrigation being the activity with the highest demand. Since water is an extremely important resource and is widely used in agriculture, water reuse has become a highly studied practice in recent years. This research aims to identify water reuse practices used in irrigation in the agricultural sector of the municipality of Aurora – Santa Catarina (SC). Data collection was performed with a form containing seventeen questions, presented to farmers in the second half of October 2014. As a result, the farmers of Aurora reused water in irrigation indirectly.